Effect of Pb:S molar ratio in precursor solution on the properties of lead sulphide thin films by ultrasonic spray pyrolysis. (15th November 2017) - Sarica, Emrah; Bilgin, Vildan
Abstract: In this work, PbS thin films were deposited onto glass substrate at 225 °C by spraying precursor solution prepared with different molar ratio of lead acetate and thiourea as a source of Pb 2+ and S 2- respectively in order to investigate the effect of Pb:S molar ratio in the precursor solution on the physical properties of PbS thin films. Structural investigations carried out by X-ray diffractometer have shown that all films have fcc cubic structure and the average crystal size increased from 11 nm to 25 nm with the increasing the thiourea ratio in the precursor solution. In order to analyze the surface morphology of PbS thin films, AFM and SEM images were taken and elemental analysis of the films was performed by EDS. Optical transmittance and absorption spectra show that all deposited films have fairly low transmittance and high absorbance in the visible region. Additionally, it was determined that optical band gap of the deposited films were varied between 1.18 eV and 1.37 eV. As a consequence of electrical investigations, it was seen that all films have p-type conductivity and electrical resistivity decreased by increasing thiourea molar ratio in the precursor solution. All examinations have revealed that the molar ratio of lead acetate and thiourea has a significant effect on the physical properties of PbS thin films.